PENGARUH BRAND AWARENESS DAN PRODUCT QUALITY TERHADAP KEPUTUSAN PEMBELIAN PADA SEPATU MERK VANS DI KOTA SURABAYA - Rachmawan, Muhammad Andrino; Maduwinarti, Ayun; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
his study entitled "The Influence of Brand Awareness and Product Quality on Purchasing Decisions on Vans Brand Shoes in the City of Surabaya". Changes in people’s needs and trends in the fashion sector, especially in big cities like Surabaya. People who follow these changes tend to buy fashion items from well-known brands to make them look cool. Currently shopping for fashion has turned into part of the lifestyle. Likewise with current shoe trends, especially among young people. They are willing to look cool by buying the latest released shoes. Due to the limitations of millennials with limited pocket money, it is difficult to get or buy original shoes at quite high prices. The purpose of this study was to determine the effect of Brand Awareness (X1) and Product Quality (X2) on Purchasing Decisions (Y) on Vans Brand Shoes in the City of Surabaya. The research methodology used is quantitative, using an online questionnaire through the Google Form. The sampling technique used purposive sampling with a total of 100 respondents to be sampled. The data analysis technique used is multiple regression analysis. The results of this study indicate (1) Brand Awareness has a significant effect on Purchase Decision on Vans brand shoes, (2) Product Quality has a significant effect on Purchase Decision on Vans brand shoes.